Pelatihan Pembelajaran Daring Berbasis Zoom untuk Guru MA NW Kabar Kabupaten Lombok Timur - Alpiana Hidayatulloh; Khairul Rijal; Indah Arry Pratama; Bq. Malikah, Hr (Jurnal Pengabdian UNDIKMA, 2021)
This community service aims to provide training on the use of the zoom application as a medium for carrying out the online learning process, this training was attended by MA NW Kabar teachers, Sakra District, East Lombok Regency. In this training the community service implementation team collaborates with information and computer engineering teachers. The training method used is direct training using the instruments provided after the training. The target achieved after this training is the understanding of the teacher using the zoom application as an online learning medium. As a result of this training, 80% of teachers in each subject use zoom as a medium to carry out the learning process online.